Geology and Geochemistry of Batuan Gunungapi Walimbong Formation Balepe Area Tana Toraja Regency South Sulawesi Province - Idham, Virly Fakhriyah Uzdah; Azikin, Busthan; Tonggiroh, Adi (CV Insight Publisher, 2025)
The study area is located in the Regional Geological Sheet of Majene and Western Palopo, precisely administratively, the research location is located in the Balepe Area, Malimbong Balepe District, Tana Toraja Regency, South Sulawesi Province and astronomically located at the coordinates 119°39'20' 'E - 119°43'20'' E (East Longitude) and 03°03'25'' S - 03°06'25'' S (South Latitude). The purpose of the study was to find out the type and affinity of magma, the naming of rocks based on chemical composition, and the evolution of magma in the study area. The methods used are field observations and data collection, petrographic analysis, and geochemistry using XRF (X-Ray Fluorescence spectrometry). The data was processed using GCDKIT Software. Based on the results of geochemical analysis on the four rock samples, the rock types were based on Total Alkaline Silica (TAS), namely trachy basalt, basalt, rhyolite, and dacite with magma affinity, namely Shoshonite Series and High-K calc-alkaline Series. Petrographic analysis in the form of naming rocks using the Pettijohn (1975) classification, namely lithic tuff, crystal vitric tuff, vitric crystal tuff, and vitric crystal tuff. The evolution of magma in the study area in the diagram of the variation of the content of major elements against SiO2 compounds shows that some of the main elements are systematically differentiated and some are not systematic.